2022
DOI: 10.1002/bmc.5460
|View full text |Cite
|
Sign up to set email alerts
|

Rapid analysis of components in Qizhiweitong tablets and plasma after oral administration in rats by UPLC–Q‐TOF–MS/MS based on a self‐developed database

Abstract: Qizhiweitong is a famous traditional Chinese prescription medicine. It has been used to treat various stomach disorders, such as functional dyspepsia, chronic gastritis and intestinal stress syndrome, for a long time and gives favorable therapeutic effects in clinical settings. However, its chemical composition and possible bioactive components are not completely known. In the present study, we used ultra-performance liquid chromatography coupled with quadrupole time-of-flight tandem mass spectrometry (UPLC-QT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/ph17060727/s1, Figure S1: Chemical structures of the 13 reference standard compounds selected as marker compounds for the quality control of YWS; Figure S2 4), 4-hydroxycinnamic acid (5), liquiritin apioside (6), vanillin (7), liquiritin (8), ferulic acid (9), narirutin (10), naringin (11), isoliquiritin (12), ononin (13), neoponcirin (14), liquiritigenin (15), poncirin (16), baicalin (17), wogonoside (18), baicalein (19), isoliquiritigenin (20), wogonin (21), glycyrrhizin (22), and γ-oryzanol (23); 5), ononin (6), baicalin (7), poncirin (8), wogonoside (9), baicalein (10), isoliquiritigenin (11), glycyrrhizin (12), and wogonin (13); Figure S4: Comparison of HPLC-PDA chromatograms according to the column temperatures of the 13 selected marker compounds: 35 • C (A), 40 • C (B), 45 • C (C), and 50 • C (D). Liquiritin apioside (1), liquiritin (2), 4-hydroxycinnamic acid (3), narirutin (4), naringin (5), ononin (6), baicalin (7), poncirin (8), wogonoside (9), baicalein (10), isoliquiritigenin (11), glycyrrhizin (12), and wogonin (13); Figure S5: Comparison of HPLC-PDA chromatograms according to the type of acid for the 13 selected marker compounds: 0.1% (v/v)…”
Section: Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following supporting information can be downloaded at: https:// www.mdpi.com/article/10.3390/ph17060727/s1, Figure S1: Chemical structures of the 13 reference standard compounds selected as marker compounds for the quality control of YWS; Figure S2 4), 4-hydroxycinnamic acid (5), liquiritin apioside (6), vanillin (7), liquiritin (8), ferulic acid (9), narirutin (10), naringin (11), isoliquiritin (12), ononin (13), neoponcirin (14), liquiritigenin (15), poncirin (16), baicalin (17), wogonoside (18), baicalein (19), isoliquiritigenin (20), wogonin (21), glycyrrhizin (22), and γ-oryzanol (23); 5), ononin (6), baicalin (7), poncirin (8), wogonoside (9), baicalein (10), isoliquiritigenin (11), glycyrrhizin (12), and wogonin (13); Figure S4: Comparison of HPLC-PDA chromatograms according to the column temperatures of the 13 selected marker compounds: 35 • C (A), 40 • C (B), 45 • C (C), and 50 • C (D). Liquiritin apioside (1), liquiritin (2), 4-hydroxycinnamic acid (3), narirutin (4), naringin (5), ononin (6), baicalin (7), poncirin (8), wogonoside (9), baicalein (10), isoliquiritigenin (11), glycyrrhizin (12), and wogonin (13); Figure S5: Comparison of HPLC-PDA chromatograms according to the type of acid for the 13 selected marker compounds: 0.1% (v/v)…”
Section: Supplementary Materialsmentioning
confidence: 99%
“…Many studies have reported on ways to improve FD symptoms or develop treatments using traditional herbal medicines [ 11 , 12 , 13 , 14 ] or herbal medicine prescriptions [ 6 , 15 , 16 , 17 ]. Recently, Hwang et al reported the effectiveness of YWS in improving gastric emptying through modulation of the ghrelin pathway in loperamide-induced FD using a mouse model [ 5 ].…”
Section: Introductionmentioning
confidence: 99%